THE SOCIAL REPRESENTATION OF THE LEISURE FOR LEADING WOMEN WITHOUT LAND (Fiep Bulletin - online, 2014)
The objective of the study was to identify the instituted social representations in the imaginary ones of Women Without Land on the leisure. We work with leading women of the movement - Chico Encampment Mendes de Matelândia/Pr - in function to be responsible for the actions the politics of the organization, formadoras of opinion and for the disciplinamento of the encampment. We made use of the technique of the half-structuralized interview in order better to absorb the speeches of the social atoras. From the speeches it was possible to identify that it has little practical of leisure, therefore the priority is the work politician. Free time was represented as the "time of the barraco". The representation on leisure sends practical the solidary ones, being that the central nucleus of the representation presents as anchorage the calls values humanists. The women present conscience of the importance of the leisure, but, its objective conditions and subjective of life they make them to occupy its time, prioritariamente, with practical come back toward the education, formation and consolidation politics of the movement.
Keywords: Leisure; Women; Movement of the Agricultural Workers Without Land